Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics: Student Research Workshop 2022
DOI: 10.18653/v1/2022.acl-srw.26
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Cross-lingual Text Detoxification with Large Multilingual Language Models.

Abstract: Detoxification is a task of generating text in polite style while preserving meaning and fluency of the original toxic text. Existing detoxification methods are designed to work in one exact language. This work investigates multilingual and cross-lingual detoxification and the behavior of large multilingual models like in this setting. Unlike previous works we aim to make large language models able to perform detoxification without direct fine-tuning in given language. Experiments show that multilingual models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In most TST papers (e.g. [28,13,22]) the methods are evaluated with the combination of the measures that score the basic TST properties: style accuracy, content preservation, and fluency. Our work is dedicated to formality transfer with an additional task to preserve particular slots.…”
Section: Discussionmentioning
confidence: 99%
“…In most TST papers (e.g. [28,13,22]) the methods are evaluated with the combination of the measures that score the basic TST properties: style accuracy, content preservation, and fluency. Our work is dedicated to formality transfer with an additional task to preserve particular slots.…”
Section: Discussionmentioning
confidence: 99%
“…For text detoxification, only in (Moskovskiy et al, 2022) cross-lingual setup was explored through the translation of inputs and outputs of a monolingual system. It has been shown that detoxification trained for English using a multilingual Transformer is not working for Russian (and vice versa).…”
Section: Cross-lingual Knowledge Transfermentioning
confidence: 99%
“…Afterwards, there were experiments in multilingual detoxification. However, crosslingual transfer between languages with multilingual seq2seq models was shown to be a challenging task (Moskovskiy et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For languages with unique linguistic characteristics and cultural contexts [8], such as Vietnamese, acquiring suitable data becomes a formidable challenge. Being a tonal language rich in diacritics and idiomatic expressions, it makes the collection and curation of data in Vietnamese even more critical due to its distinctiveness from languages like English [9]. This paper embarks on an exploration of the intricacies involved in collecting and curating data for fine-tuning Vietnamese language models.…”
Section: Introductionmentioning
confidence: 99%